2013
DOI: 10.1261/rna.036418.112
|View full text |Cite
|
Sign up to set email alerts
|

RNAi pathways contribute to developmental history-dependent phenotypic plasticity in C. elegans

Abstract: Early environmental experiences profoundly influence adult phenotypes through complex mechanisms that are poorly understood. We previously showed that adult Caenorhabditis elegans that transiently passed through the stress-induced dauer larval stage (post-dauer adults) exhibit significant changes in gene expression profiles, chromatin states, and life history traits when compared with adults that bypassed the dauer stage (control adults). These wild-type, isogenic animals of equivalent developmental stages exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 94 publications
2
52
0
Order By: Relevance
“…Although dauer-inducing environmental conditions are detected by a complex network of chemosensory neurons found in the head of worms, little is known about the concurrent integration of these signals, and whether the dauer formation triggers may have distinct effects at a molecular level. We have shown previously that postdauer adults that experienced high pheromone conditions are phenotypically distinct from adults that bypassed the dauer stage, and that these effects are partially dependent upon RNAi pathways (Hall et al 2010(Hall et al , 2013. Our data presented here suggest the intriguing possibility that RNAi pathways may mediate distinct effects on gene expression in postdauer animals that experienced different environmental stresses.…”
Section: Rnai Is Required In Neurons For Behavioral Adaptation To Envmentioning
confidence: 50%
See 1 more Smart Citation
“…Although dauer-inducing environmental conditions are detected by a complex network of chemosensory neurons found in the head of worms, little is known about the concurrent integration of these signals, and whether the dauer formation triggers may have distinct effects at a molecular level. We have shown previously that postdauer adults that experienced high pheromone conditions are phenotypically distinct from adults that bypassed the dauer stage, and that these effects are partially dependent upon RNAi pathways (Hall et al 2010(Hall et al , 2013. Our data presented here suggest the intriguing possibility that RNAi pathways may mediate distinct effects on gene expression in postdauer animals that experienced different environmental stresses.…”
Section: Rnai Is Required In Neurons For Behavioral Adaptation To Envmentioning
confidence: 50%
“…Although adults that passed through, or bypassed, the dauer stage appear morphologically similar, we previously showed that C. elegans retain a cellular memory of their developmental history that is reflected in changes in gene expression, genome-wide chromatin states, and life history traits (Hall et al 2010). Furthermore, we have shown that RNAi pathways are a major contributor to developmental history-dependent phenotypes in adults (Hall et al 2013). However, the role of RNAi pathways in regulating environmentally induced phenotypic plasticity during early larval stages is unknown.…”
mentioning
confidence: 98%
“…In nature, normal C. elegans harbors low desiccation tolerance, while diapausing worms own high tolerance (Erkut et al, 2011;Hall et al, 2013). Diapausing C. elegans enter a state of anhydrobiosis to maintain subsistence under dry conditions.…”
Section: Discussionmentioning
confidence: 99%
“…elegans is capable of spending an extensive period in the dauer stage without adverse effects on its postrecovery reproductive fitness. In fact, studies have demonstrated that lifespan and brood size are both marginally, yet significantly, enhanced following passage through dauer (Hall et al 2010(Hall et al , 2013.…”
Section: Din-1s Exhibits Dauer-dependent Reproductive Defectsmentioning
confidence: 99%
“…elegans is capable of spending an extensive period in the dauer stage without adverse effects on its postrecovery reproductive fitness. In fact, studies have demonstrated that lifespan and brood size are both marginally, yet significantly, enhanced following passage through dauer (Hall et al 2010(Hall et al , 2013.Over 90% of daf-2 control animals recover from the dauer stage to become healthy, egg-laying adults regardless of whether they have previously spent 1, 3, or 7 days as dauer larvae (Figure 4). Although din-1S; daf-2 animals typically grow to become healthy adults, they display severe reproductive defects during the adult stage if they transit through dauer.…”
mentioning
confidence: 98%